Wellbeing of School Communities in the Context of COVID-19 Pandemic: A Qualitative Study in Chilean Low-SES Schools - López, Verónica; Ramírez, Lorena; López-Concha, Romina; Ascorra, Paula; Álvarez, Juan Pablo; Carrasco-Aguilar, Claudia; Jervis, Pamela; Squicciarini, Ana María; Simonsohn, Ariela; Contreras, Tabata; Opazo, Héctor (Frontiers in Psychology, 2022)
The COVID-19 pandemic continues to impact schools and how education is conveyed to students. One of the aspects that has gained strength is supporting the well-being of educational communities. The purpose of this study is to describe and understand the construction of school well-being during the pandemic, based on the notion of collective and sustainable well-being. Through a qualitative design, we conducted a study in four Chilean low-SES schools which run a school mental health program. A total of 41 in-depth interviews and one group interview were conducted with students, parents, school principals, teachers, psychosocial professionals, and officials. Thematic content analyses show that, when in the face of a major crisis, schools become a channel of hope and strive to protect students’ and teachers’ well-being. However, participants highlight six necessary conditions to promote and protect the well-being of the school community in the context of the COVID-19 pandemic: i) assuring digital connectivity for all students; ii) coordinated work with families; iii) coordinated work at school; iv) strengthening networks; v) curriculum adaptation and diversified pedagogical strategies; and vi) emotional support towards teachers, families, and students. We discuss the need to consider these crucial conditions in the design, implementation, and evaluation of educational policies and interventions that seek to favor school well-being during crises.